Organizing theoretical learning along with real objects and arranging theoretical learning along with pictures of invertebrate anatomy using brainstorming method for 2nd year chemistry students, 12 + 4 system, 3rd semester 2019-2020 at Luang Prabang Teach - Khamta, Duangmala (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this research is (1) to compare the learning results of second year chemistry students who organize theoretical learning along with real objects and organize theoretical learning along with pictures through brainstorming teaching method. (2) To compare the satisfaction of the 2nd year chemistry students to the arrangement of theoretical learning along with real objects and the arrangement of theoretical learning along with pictures with brainstorming teaching method. The target group used in this research is the 2nd year students of the 12 + 4 systems, the 3rd semester of the 2019-2020 school year at Luang Prabang Teachers College. There are 2 classes, 24 students in each room. The total target group is 48 people with specific selection. The tools used in this research are 10 plans for learning theory along with real objects with brainstorming methods, 10 plans for learning theories with pictures using brainstorming methods, 50 items for students' academic achievement test with 4 choices, 50 items, questionnaire on student satisfaction with plans for learning theory with pictures and theory with pictures Rating Scale 5 level with 26 items. The statistics used to analyze the data are mean values, standard deviation values and hypothesis testing with t-test (Independent Samples). The results of the study on organizing theoretical learning along with real objects and organizing theoretical learning along with pictures with the brainstorming method found that: organizing theoretical learning along with objects resulted in students having higher academic success in invertebrate anatomy than students who studied with organizing theoretical learning along with pictures in invertebrate anatomy. But both groups of students are satisfied with the two learning plans. Therefore, it should be promoted to organize the learning of theory along with real objects and theory along with pictures with brainstorming methods to be used in the development of students' learning skills in the next Invertebrate Anatomy course